2014
DOI: 10.1051/matecconf/20141409003
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of secondary phases in alloy ATI 718Plus®during processing

Abstract: Abstract. ATI 718Plus R is a polycrystalline Ni-base superalloy for aero-engine disc applications, which relies on the precipitation of η-phase (Ni 6 Nb[Al,Ti], D0 24 ) at grain boundaries for resistance to intergranular failure and grain size control. The nucleation and evolution of the η particles have been examined throughout the manufacturing process. During hot working below the η solvus, existing precipitates lose their orientation relationship with the matrix and become aligned with the forging flow. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…When calculating the contribution of yield stress at room temperature, the critical radius/aging time can be found by equating the Eqs. (6) and (7).When this is applied to the current case, one finds the critical aging time to be 4000 seconds (taking β = 1 and k c = 1). However, this would not correlate with the findings of the TEM study (this will later be shown in Fig (9) where after 1200 seconds of aging it is possible to see bowing mechanism).…”
Section: Modeling the Observed Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…When calculating the contribution of yield stress at room temperature, the critical radius/aging time can be found by equating the Eqs. (6) and (7).When this is applied to the current case, one finds the critical aging time to be 4000 seconds (taking β = 1 and k c = 1). However, this would not correlate with the findings of the TEM study (this will later be shown in Fig (9) where after 1200 seconds of aging it is possible to see bowing mechanism).…”
Section: Modeling the Observed Behaviormentioning
confidence: 98%
“…Unlike alloy 718, the main strengthening phase of 718Plus T M is γ (Ni 3 [Al Nb Ti]), L12, cubic) instead of γ (Ni 3 Nb, D022, tetragonal). Above-mentioned increase of the temperature capability is believed to originate from the stability advantage of γ over γ [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous characterization of a forged component found a large variation in g area fraction from 2 area pct in the center to 9 area pct at the rim. [3] In terms of MDRX this scatter in the area fraction of g could lead to a wide scatter in grain sizes throughout the component.…”
Section: B Drx and Mdrx Of The Two-phase Microstructurementioning
confidence: 99%
“…[1,2] The g morphology depends on the thermo-mechanical history of the material and can range from small and blocky to a thin lamellar structure. [3] Such particles could influence the recrystallization characteristics of 718Plus.…”
Section: Introductionmentioning
confidence: 99%
“…Casanova et al [15] found that within the microstructure of components made with ATI 718Plus, two main morphologies co-exist together; coarse plates and thin lamellae, and the origin of these were investigated by the author. phase precipitates are present within the microstructure of the billet prior to forging as coherent thin lamellae.…”
Section: Introductionmentioning
confidence: 99%